IMPLEMENTATION OF IOT-BASED SMART AQUACULTURE TO EMPOWER NILA FARMERS IN BAGINDA VILLAGE - Abdul Muhaemin, Muhamad Nurdin; Ramdon, Edwar J.; Wahyuni, Sri; Adha, Fadhil Firdaus; Fathurrahman, Fikry (LPPM Univ. Ibn Khaldun Bogor, 2026)
This community service program was carried out at the fish farmer group (POKDAKAN) Tirta Mukti in Baginda Village, Sumedang Selatan District, with the main focus on implementing IoT-based Smart Aquaculture in a biofloc system to improve the quality and productivity of Nile tilapia culture. The situation analysis showed several priority problems: the absence of real-time water quality monitoring devices, non-systematic recording of production and feed conversion ratio (FCR), weak business management, and the absence of digital marketing and attractive, licensed processed products. The implemented method combined socialization, training, field implementation, mentoring, and sustainability planning in a participatory approach. The solutions included installation of four water quality sensors (dissolved oxygen, pH, temperature, turbidity) integrated with a web-based monitoring application (https://smartaqua.my.id/), an automatic feeder, training on biofloc and business management, preparation of simple bookkeeping templates, and development of digital marketing tools (social media, WhatsApp Business, packaging design, and PIRT draft). The results show increased partner capacity in using IoT technology, improved efficiency of feed use, more structured production and financial recording, and the initiation of online-based marketing. This program demonstrates that the integration of IoT, biofloc technology, and digital marketing can enhance productivity, added value, and sustainability of small-scale tilapia farming in rural areas.